Safety and preliminary efficacy of venetoclax with decitabine or azacitidine in elderly patients with previously untreated acute myeloid leukaemia: a non-randomised, open-label, phase 1b study. Issue 2 (February 2018) - DiNardo, Courtney D; Pratz, Keith W; Letai, Anthony; Jonas, Brian A; Wei, Andrew H; Thirman, Michael; Arellano, Martha; Frattini, Mark G; Kantarjian, Hagop; Popovic, Relja; Chyla, Brenda; Xu, Tu; et al.
Summary: Background: Elderly patients (aged ≥65 years) with acute myeloid leukaemia have poor outcomes and no effective standard-of-care therapy exists. Treatment with hypomethylating agents such as azacitidine and decitabine is common, but responses are modest and typically short-lived. The oral anti-apoptotic B-cell lymphoma 2 protein inhibitor, venetoclax, has shown promising single-agent activity in patients with relapsed or refractory acute myeloid leukaemia and preclinical data suggested synergy between hypomethylating agents and venetoclax, which led to this combination phase 1b study. Methods: Previously untreated patients aged 65 years and over with acute myeloid leukaemia who were ineligible for standard induction therapy were enrolled into this non-randomised, open-label, phase 1b study. Patients were required to have an Eastern Cooperative Oncology Group performance status of 0–2 and either intermediate-risk or poor-risk cytogenetics. Patients were enrolled into one of three groups for the dose-escalation phase of this study: group A (venetoclax and intravenous decitabine 20 mg/m 2 [days 1–5 of each 28-day cycle]), group B (venetoclax and subcutaneous or intravenous azacitidine 75 mg/m 2 [days 1–7 of each 28-day cycle]), and group C (a venetoclax and decitabine substudy with the oral CYP3A inhibitor posaconazole, 300 mg twice on cycle 1, day 21, and 300 mg once daily from cycle 1, days 22–28, to assess its effect on venetoclax pharmacokinetics). Dose escalation followed a standard 3 + 3 design with at least three evaluable patients enrolled per cohort; daily target doses of venetoclax for groups A and B were 400 mg (cohort 1), 800 mg (cohorts 2 and 3), and 1200 mg (cohort 4), and 400 mg for group C. The primary endpoints were the safety and pharmacokinetics of venetoclax plus decitabine or azacitidine, and to determine the maximum tolerated dose and recommended phase 2 dose. Secondary endpoints included the preliminary anti-leukaemic activity of venetoclax with decitabine or azacitidine through the analysis of overall response, duration of response, and overall survival. We analysed safety, pharmacokinetics, and anti-leukaemic activity in all patients who received one or more venetoclax doses. The expansion phase of the study is ongoing but is closed to accrual. This trial is registered withClinicalTrials.gov, numberNCT02203773 . Findings: 57 patients were enrolled in the study. 23 patients in group A and 22 patients in group B were enrolled between Nov 19, 2014, and Dec 15, 2015, and 12 patients in group C were enrolled between June 14, 2015, and Jan 16, 2016. As of data cutoff on June 15, 2016, the most common grade 3–4 treatment-emergent adverse events were thrombocytopenia (27 [47%] of 57 patients; nine in group A, 13 in group B, and five in group C), febrile neutropenia (24 [42%] of 57; 11 in group A, ten in group B, and three in group C), and neutropenia (23 [40%] of 57; 12 in group A, eight in group B, and three in group C). The most common serious treatment-emergent adverse event in groups A and B was febrile neutropenia (seven [30%] of 23 patients vs seven [32%] of 22), whereas in group C it was lung infection (four [33%] of 12 patients). 49 (86%) of 57 patients had treatment-related adverse events; the most common in groups A and B included nausea (12 [52%] patients vs seven [32%] patients), fatigue (six [26%] patients vs seven [32%]), and decreased neutrophil count (six [26%] patients vs six [27%]), whereas in group C the most common were nausea (seven [58%] of 12 patients), leucopenia (six [50%]), vomiting (five [42%]), and decreased platelet count (five [42%]). The maximum tolerated dose was not reached. The recommended phase 2 dose was 400 mg once a day or 800 mg with an interrupted dosing schedule (safety expansion). In total, four (7%) of 57 patients had died within 30 days of the first venetoclax dose caused by sepsis (group B), bacteraemia (group A), lung infection (group C), and respiratory failure (group A). Tumour lysis syndrome was not observed. Decitabine and azacitidine did not substantially affect venetoclax exposures. Overall, 35 (61%; 95% CI 47·6–74·0) of 57 patients achieved complete remission or complete remission with incomplete marrow recovery. In groups A and B, 27 (60%; 95% CI 44·3–74·3) of 45 patients had complete remission or complete remission with incomplete marrow recovery. Interpretation: Venetoclax plus hypomethylating agent therapy seems to be a novel, well-tolerated regimen with promising activity in this underserved patient population. Evaluation of expansion cohorts is ongoing at 400 mg and 800 mg doses using both hypomethylating agent combinations. Funding: AbbVie and Genentech.